Identification of Potential Candidate Genes of Oral Cancer in Response to Chronic Infection With Porphyromonas gingivalis Using Bioinformatical Analyses - Geng, Fengxue; Wang, Qingxuan; Li, Chen; Liu, Junchao; Zhang, Dongmei; Zhang, Shuwei; Pan, Yaping (Frontiers in Oncology, 2019)
Recent investigations revealed the relationship between chronic periodontitis, Porphyromonas gingivalis and cancer. However, host genes that change in response to chronic infection with P. gingivalis and may contribute to oral cancer have remained largely unknown. In the present study, we aimed to comprehensively analyze microarray data obtained from the chronic infection model of immortalized oral epithelial cells that were persistently exposed to P. gingivalis for 15 weeks. Using protein-protein interaction (PPI) networks and Ingenuity Pathway Analysis (IPA), we identified hub genes, major biological processes, upstream regulators and genes potentially involved in tumor initiation and progression. We also validated gene expression and demonstrated genetic alteration of hub genes from clinical samples of head and neck cancer. Overall, we utilized bioinformatical methods to identify IL6, STAT1, LYN, BDNF, C3, CD274, PDCD1LG2 and CXCL10 as potential candidate genes that might facilitate the prevention and treatment of oral squamous cell carcinoma (OSCC), the most common type of head and neck squamous cell carcinoma (HNSCC).